Keberhasilan Kebijakan Pengampunan Pajak (Tax Amnesty) di Indonesia - Budi Ispriyarso (Administrative Law and Governance Journal, 2019)
Abstract The Indonesian government has carried out a tax amnesty policy in 2016. The background for the tax amnesty policy is, among other things, the wealth of Indonesian citizens who have not or have not all been reported in the Annual Notice. Some of the objectives of the tax amnesty, among others, are in the short term to increase tax revenues, the long-term goals include strengthening domestic liquidity, increasing investment, accelerating tax reforms and increasing tax revenues. The problem is whether the tax amnesty carried out by the Indonesian government succeeded, what was the negative side of the implementation of the tax amnesty. Tax amnesty in Indonesia from ransom receipts specifically from the declaration can be said to be successful, but the repatriation failed and the number of participants participating in the tax amnesty program was not as expected. The negative side of the tax amnesty is the tax amnesty, giving rise to a sense of injustice especially for obedient taxpayers, the tax amnesty can lead to non-compliance of taxpayers because they hope that a future tax amnesty and tax amnesty are not in accordance with the principles of law enforcement. Keywords: Tax Amnesty, success and ransom Abstrak Pemerintah Indonesia telah melakukan kebijakan pengampunan pajak (Tax Amnesty ) pada tahun 2016. Latar belakang dilakukannya kebijakan tax amnesty tersebut, antara lain adalah karena banyaknya harta warga negara Indonesia yang belum atau belum semuanya dilaporkan dalam Surat Pemeritahuan Tahunan. Beberapa tujuan tax amnesty, antara lain adalah dalam jangka pendeknya meningkatkan penerimaan perpajakan, tujuan jangka panjangnya antara lain adalah memperkuat likuiditas domestik, peningkatan investasi, mempercepat reformasi perpajakan dan meningkatkan penerimaan pajak. Permasalahannya adalah apakah tax amnesty yang dilakukan pemerintah Indonesia berhasil, apa saja yang menjadi sisi negatif dari pelaksanaan tax amnesty tersebut. Tax amnesty di Indonesia dari penerimaan tebusan khususnya dari deklarasi dapat dikatakan berhasil, namun dari repatriasinya gagal dan dari jumlah peserta yang mengikuti program tax amnesty  tidak seperti yang diharapkan. Sisi negatif dari tax amnesty adalah tax amnesty, menimbulkan rasa ketidak adilan khususnya bagi wajib pajak yang patuh, tax amnesty dapat menimbulkan ketidakpatuhan wajib pajak karena berharap ada tax amnesty di masa yang akan datang dan tax amnesty tidak sesuai dengan prinsip  penegakan hukum. Kata kunci : Tax Amnesty, keberhasilan dan  uang tebusan